Old, New, and Future Food Policy Before and After the Covid-19 Pandemic in Indonesia - Yunianto, Andi Eka; Martianto, Djarat; Husna, Arfah; Putri, Widya Ayu Kurnia; Puspitasari, Ikha Deviyanthi; Susilowati, Erna; Ardhian, David (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2023)
This article aimed to identify aspects of Old, New, and Future Food Policy before and after the Covid-19 pandemic. before and after the COVID-19 pandemic.  The method used was a Narrative review using a comprehensive and descriptive approach through a literature search. Data searches were conducted through online instruments using Pubmed, ScienceDirect and Google Scholar published from 2003-2023. The search was conducted using keywords related to factors driving changes in the nature of food and nutrition policies based on Maxwell's theory. The COVID-19 pandemic has affected food insecurity supported by restrictions on economic activity and mobility imposed by the government which have led to economic contraction and job losses, which in turn can affect household access to food. Policies after the COVID-19 pandemic regarding food related to aspects of food availability, aspects of food access, and aspects of food utilization as well as the importance of stakeholders in the success of food policy programs in Indonesia.